2001
DOI: 10.1097/00005176-200102000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Residual Intestinal Disease After Milk Allergy in Infancy

Abstract: In a certain proportion of subjects with CMA in infancy, GI intolerance seems to persist even after small-dose tolerance has been achieved. The intestinal symptoms and the increased prevalence of lactose intolerance may be caused by a disturbance of the surface epithelial cells--a state to which the authors refer as residual intestinal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…The first abates, while the latter does not, at least not in all patients, the reactivity persisting on the mucosa of the GI tract giving only GI symptoms and mainly no skin or other symptoms [10,11]. We speculate that in the present material the increase in GI symptoms may be partly due to this reactivity, though we did not test these subjects.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The first abates, while the latter does not, at least not in all patients, the reactivity persisting on the mucosa of the GI tract giving only GI symptoms and mainly no skin or other symptoms [10,11]. We speculate that in the present material the increase in GI symptoms may be partly due to this reactivity, though we did not test these subjects.…”
Section: Discussionmentioning
confidence: 52%
“…There is now increasing evidence showing that subjects with untreated food allergy have the same type of skewing of the immune response as those with celiac disease (CD), a state increasing the risk of autoimmune disorders [7][8][9]. Moreover, we recently found that food allergy in infancy does not remit as was previously believed, the immune reactivity on the mucosa of the gastrointestinal tract apparently remaining [10,11]. Following these observations we hypothesized that the subjects with infantile onset atopic dermatitis, like subjects with CD, might be at risk of eventually manifesting autoimmune and/or immune-mediated GI disorders more than expected.…”
Section: Introductionmentioning
confidence: 99%
“…Many autoimmune diseases have in common many of the features of the immune response with atopic disorders [23,24]. Moreover, they found that food allergy in infancy does not remit the immune reactivity on the mucosa of the gastrointestinal tract [25,26]. So the persistent and exaggerated immune response on the gastrointestinal mucosa and related lymphoproliferative system due to untreated food allergy could be the central pathogenic mechanism for this co-occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…This is still the object of numerous studies on the youngest children with food hypersensitivity and GER, whereas in older children with persistent allergy [1,13,14,16,22,25,27,28].…”
Section: Introductionmentioning
confidence: 99%